0.24x−0.74=−1.1

0.24x=
Add 0.74 to both sides.
x=
Divide both sides by 0.24.

3 answers

Let's solve the equation step by step.

Starting with the equation:

\[ 0.24x - 0.74 = -1.1 \]

  1. Add 0.74 to both sides:

\[ 0.24x - 0.74 + 0.74 = -1.1 + 0.74 \]

This simplifies to:

\[ 0.24x = -0.36 \]

  1. Divide both sides by 0.24:

\[ x = \frac{-0.36}{0.24} \]

Now calculate that division:

\[ x = -1.5 \]

So the final solution is:

\[ x = -1.5 \]

−3x−9=−21
−3x=
Add 9 to both sides.
x=
Divide both sides by −3.

Let's solve the equation step by step.

Starting with the equation:

\[ -3x - 9 = -21 \]

  1. Add 9 to both sides:

\[ -3x - 9 + 9 = -21 + 9 \]

This simplifies to:

\[ -3x = -12 \]

  1. Divide both sides by -3:

\[ x = \frac{-12}{-3} \]

This simplifies to:

\[ x = 4 \]

So the final solution is:

\[ x = 4 \]